BUSINESS FINANCES, FINANCINAL TECHNOLOGY, AND CAPITAL STRUCTURE - A. Volodin (Вестник университета)
We distinguish the theoretical issues of the Category business finance. Considered some problems of the nature and definition of finance role of the financial strategy in the overall strategy of the enterprise. The main thing was shown is a technique to identify the impact of the capital structure on the company’s profitability of its own funds.